Radiopacity and cytotoxicity of Portland cement associated with niobium oxide micro and nanoparticles - Mestieri, Leticia Boldrin [UNESP]; Tanomaru-Filho, Mário [UNESP]; Gomes-cornélio, Ana Livia [UNESP]; Salles, Loise Pedrosa [UNESP]; Bernardi, Maria Inês Basso; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Faculdade De Odontologia De Bauru - USP, 2014)
ObjectiveMineral Trioxide Aggregate (MTA) is composed of Portland Cement (PC) and bismuth oxide (BO). Replacing BO for niobium oxide (NbO) microparticles (Nbµ) or nanoparticles (Nbη) may improve radiopacity and bioactivity. The aim of this study was to evaluate the radiopacity and cytotoxicity of the materials: 1) PC; 2) White MTA; 3) PC+30% Nbµ; 4) PC+30% Nbη. Material and MethodFor the radiopacity test, specimens of the different materials were radiographed along an aluminum step-wedge. For cell culture assays, Saos-2 osteoblastic-cells (ATCC HTB-85) were used. Cell viability was evaluated through MTT assay, and bioactivity was assessed by alkaline phosphatase activity assay. ResultThe results demonstrated higher radiopacity for MTA, followed by Nbµ and Nbη, which had similar values. Cell culture analysis showed that PC and PC+NbO associations promoted greater cell viability than MTA. ConclusionIt was concluded that the combination of PC+NbO is a potential alternative for composition of MTA.
Keywords: Silicate cement; Niobium; Nanotechnology